2017
DOI: 10.15294/jejak.v10i2.11291
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact Analysis of Relocation Five Feet Vendors in Purwokerto

Abstract: This study aimed to analyze income, expenses, and social environment of street vendors between before and after the relocation to Pratistha Harsha. Collecting data is using interview, observation and literature study techniques. The respondents were selected namely Pratistha Harsha Chief Manager, Chairman of The Pratistha Harsha Society, Pratistha Harsha vendors culinary. Population of street vendors who relocated to Pratistha Harsha are 65 peoples and sample are 40 seller respondents. Selection of the sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…What would have contributed to the increase in the expenses is the cost of handling their inventories and the additional cost of transporting the goods of the vendors away from the main public route of public utilities. This experience is similar to that of the relocated vendors in Purwokerto, Java, Indonesia (Purnomo, 2017).…”
Section: Extent Of Economic Implications Of Relocation Of Street Vendorssupporting
confidence: 73%
See 3 more Smart Citations
“…What would have contributed to the increase in the expenses is the cost of handling their inventories and the additional cost of transporting the goods of the vendors away from the main public route of public utilities. This experience is similar to that of the relocated vendors in Purwokerto, Java, Indonesia (Purnomo, 2017).…”
Section: Extent Of Economic Implications Of Relocation Of Street Vendorssupporting
confidence: 73%
“…286 (otherwise known as the Ordinance Establishing Vendors' Plaza and Jeepney Terminal at the Reclamation Area). However, Purnomo (2017) found increases in the expenses, including labor, transportation, raw materials, electricity, rent, hygiene, garbage, and community fees after the relocation.…”
Section: Extent Of Economic Implications Of Relocation Of Street Vendorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The forbidden public areas include sidewalks, shoulders, roadside near rivers, government offices, and more. Purnomo (2017) in his research found that street vendors in Purwokerto use public space such as sidewalks and places around the market. The street vendors in Semarang also occupy crowded public spaces such as office areas, hospitals, traditional markets, supermarkets and entertainment venues.…”
Section: Introductionmentioning
confidence: 99%